Experimental study on foam glass prepared by hydrothermal hot pressing-calcination technique using waste glass and fly ash. Issue 20 (15th October 2021) - Song, Huiping; Chai, Chunjing; Zhao, Zhonghe; Wei, Lifang; Wu, Haibin; Cheng, Fangqin
Abstract: Foam glass is a lightweight and high-strength building and decoration material with superior performance in heat insulation, sound absorption, moisture resistance and fire protection. The use of waste glass powder and fly ash to prepare foam glass is one of the most important ways to utilize solid waste as a resource. In this study, waste glass powder and fly ash were used as raw materials to prepare foam glass by a hydrothermal hot pressing–calcination method. The effects of fly ash content (0 wt%, 10 wt%, 20 wt%, 30 wt%), heating rate (1 °C/min, 3 °C/min, 5 °C/min, 8 °C/min, 10 °C/min) and calcination temperature (600 °C, 700 °C, 750 °C, 800 °C, 850 °C, 900 °C) on the microscopic morphology, density, compressive strength, porosity and other properties of the foam glass samples were studied. Their microstructure and morphology were analyzed by thermogravimetric analysis–mass spectrometry, X-ray diffraction, scanning electron microscopy and Fourier transform infrared spectroscopy. At a fly ash content of 10 wt%, the heating rate was 5 °C/min, the calcination temperature was 800 °C, the foam glass density was 0.3 g/cm 3, the compressive strength was 1.65 MPa, the total porosity was 75.5%, and the effective thermal conductivity was 0.206 W/m·K. The effective thermal conductivity models of the composite materials were used to verify the experimental data. The relationship between the thermal conductivity of foam glass materials and the related influencing factors was investigated.